Nab-paclitaxel plus gemcitabine versus nab-paclitaxel plus gemcitabine followed by FOLFIRINOX induction chemotherapy in locally advanced pancreatic cancer (NEOLAP-AIO-PAK-0113): a multicentre, randomised, phase 2 trial. (February 2021) - Kunzmann, Volker; Siveke, Jens T; Algül, Hana; Goekkurt, Eray; Siegler, Gabriele; Martens, Uwe; Waldschmidt, Dirk; Pelzer, Uwe; Fuchs, Martin; Kullmann, Frank; Boeck, Stefan; Ettrich, Thomas J; et al.
Summary: Background: The optimal preoperative treatment for locally advanced pancreatic cancer is unknown. We aimed to compare the efficacy and safety of nab-paclitaxel plus gemcitabine with nab-paclitaxel plus gemcitabine followed by fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOLFIRINOX) as multidrug induction chemotherapy regimens in locally advanced pancreatic cancer. Methods: In this open-label, multicentre, randomised phase 2 study, done at 28 centres in Germany, eligible patients were adults (aged 18–75 years) with an Eastern Cooperative Oncology Group performance status of 0 or 1 and histologically or cytologically confirmed, treatment-naive locally advanced pancreatic adenocarcinoma, as determined by local multidisciplinary team review. After two cycles of nab-paclitaxel 125 mg/m 2 plus gemcitabine 1000 mg/m 2 (administered intravenously on days 1, 8, and 15 of each 28-day cycle), patients without progressive disease or unacceptable adverse events were randomly assigned (1:1) to receive either two additional cycles of nab-paclitaxel plus gemcitabine (nab-paclitaxel plus gemcitabine group) or four cycles of sequential FOLFIRINOX (oxaliplatin 85 mg/m 2, leucovorin 400 mg/m 2, irinotecan 180 mg/m 2, fluorouracil 400 mg/m 2 by intravenous bolus followed by a continuous intravenous infusion of 2400 mg/m 2 for 46 h on day 1 of each 14-day cycle; sequential FOLFIRINOX group). Randomisation was done by the clinical research organisation on request of the trial centre using a permuted block design (block size 2 and 4). Patients, investigators, and study team members were not masked to treatment allocation. The primary endpoint was surgical conversion rate (complete macroscopic tumour resection) in the randomised population by intention-to-treat analysis, which was assessed by surgical exploration in all patients with at least stable disease after completion of induction chemotherapy. This trial is registered with ClinicalTrials.gov, NCT02125136 . Findings: Between Nov 18, 2014, and April 27, 2018, 168 patients were registered and 130 were randomly assigned to either the nab-paclitaxel plus gemcitabine group (64 patients) or the sequential FOLFIRINOX group (66 patients). Surgical exploration after completed induction chemotherapy was done in 40 (63%) of 64 patients in the nab-paclitaxel plus gemcitabine group and 42 (64%) of 66 patients in the sequential FOLFIRINOX group. 23 patients in the nab-paclitaxel plus gemcitabine group and 29 in the sequential FOLFIRINOX group had complete macroscopic tumour resection, yielding a surgical conversion rate of 35·9% (95% CI 24·3–48·9) in the nab-paclitaxel plus gemcitabine group and 43·9% (31·7–56·7) in the sequential FOLFIRINOX group (odds ratio 0·72 [95% CI 0·35–1·45]; p=0·38). At a median follow-up of 24·9 months (95% CI 21·8–27·6), median overall survival was 18·5 months (95% CI 14·4–21·5) in the nab-paclitaxel plus gemcitabine group and 20·7 months (13·9–28·7) in the sequential FOLFIRINOX group (hazard ratio 0·86 [95% CI 0·55–1·36]; p=0·53). All other secondary efficacy endpoints, such as investigator-assessed progression-free survival, radiographic response rate, CA 19-9 response rate, and R0 resection rate, were not significantly different between the two treatment groups except for improved histopathological downstaging in evaluable resection specimens from the sequential FOLFIRINOX group (ypT1/2 stage: 20 [69%] of 29 patients in the sequential FOLFIRINOX group vs four [17%] of 23 patients in the nab-paclitaxel plus gemcitabine group, p=0·0003; ypN0 stage: 15 [52%] of 29 patients in the sequential FOLFIRINOX group vs four [17%] of 23 patients in the nab-paclitaxel plus gemcitabine group, p=0·02). Grade 3 or higher treatment-emergent adverse events during induction chemotherapy occurred in 35 (55%) of 64 patients in nab-paclitaxel plus gemcitabine group and in 35 (53%) of 66 patients in the sequential FOLFIRINOX group. The most common of which were neutropenia (18 [28%] in nab-paclitaxel plus gemcitabine group, 16 [24%] in the sequential FOLFIRINOX group), nausea and vomiting (two [3%] in nab-paclitaxel plus gemcitabine group, eight [12%] in the sequential FOLFIRINOX group), and bile duct obstruction with cholangitis (six [9%] in nab-paclitaxel plus gemcitabine group, seven [11%] in the sequential FOLFIRINOX group). No deaths were caused by treatment-related adverse events during the induction chemotherapy phase. Interpretation: Our findings suggest that nab-paclitaxel plus gemcitabine is similarly active and safe as nab-paclitaxel plus gemcitabine followed by FOLFIRINOX as multidrug induction chemotherapy regimens for locally advanced pancreatic cancer. Although conversion to resectability was achieved in about a third of patients, additional evidence is required to determine whether this translates into improved overall survival. Funding: Celgene.